Pengaruh Produk Domestik Regional Bruto dan Jumlah Penduduk Terhadap Pendapatan Asli Daerah Kabupaten Mimika - mawar, Mawar; Sroyer, Siska (STIE Jambatan Bulan, 2021)
This study aims to analyze the significance of the influence of GDP and Population partially on the Original Income of Mimika Regency, and to analyze the significance of the influence of GDP and Population simultaneously on the Original Income of Mimika Regency. The data used in this study are secondary data obtained from BPS Mimika Regency and Mimika District Financial and Asset Management Agency. To analyze the data used multiple linear regression analysis. The results showed that: (a) GDP had a negative and insignificant effect on the Original Revenue of Mimika Regency; (b) The number of residents has a positive and significant effect on the Original Income of Mimika Regency; (c) GDP and Population simultaneously have a significant impact on the Original Revenue of Mimika Regency.